In-PREP: a new learning design framework and methodology applied to a relational care training intervention for healthcare assistants - Heather Wharrad; Sophie Sarre; Justine Schneider; Jill Maben; Clare Aldus; Elaine Argyle; Anthony Arthur (BMC, 2020)
Abstract Background 'Older People's Shoes' is a training intervention designed for healthcare assistants (HCAs) to improve the relational care of older people in hospital. The intervention formed part of a broader evaluation, in this paper we describe its development from a learning design and methodological perspective. Methods Learning theory and an instructional design model were key components of the In-PREP (Input, Process, Review and Evaluation, Product) development methodology used in the design of the 'Older People's Shoes' training intervention to improve the delivery of relational care by front-line hospital staff. An expert panel, current evidence, and pedagogical theory were used to co-design a training programme tailored to a challenging work environment and taking account of trainees' diverse educational experience. Peer review and process evaluation were built into the development model. Results In-PREP provided a methodological scaffold for producing evidence-based, peer-reviewed, co-designed training. The product, 'Older People's Shoes', involved a one-day Train the Trainers event, followed by delivery of a two-day, face-to-face training programme by the trainers, with accompanying handbooks underpinned by a range of digital resources. Evaluation found the approach met learner needs, was applicable in practice and won approval from trainers. Discussion In-PREP enables high quality learning content, alignment with learner needs and a product that is relevant, practical and straightforward to implement.